Estimation of residuals for the homogenized solution of quasi-periodic media. (October 2018) - Cluni, F.; Gusella, V.
Abstract: In this work we analyze the convergence of the elastic coefficients in terms of the residuals as the dimensions of the sample of a random two-dimensional medium vary. In particular, the case of the masonry material which can be considered a heterogeneous solid with two phases (stones or bricks and mortar) is taken into account. In particular, we consider a masonry which presents a quasi-periodic micro-structure. A procedure of numerical generation of wall portions has been developed which takes into account not only the scale ratio but also the mechanical ratio and the geometrical ratio. The convergence of residuals has been highlighted in terms of probability density function and statistical moments, up to the second order, of the stiffness coefficients and of the log-Euclidean distance between the masonry samples and the closest isotropic material.